Extract, Transform, Load Monitoring sales Multi Marketplace - Leonardus Adityo Toto Pratomo; Deni Mahdiana (Universitas Negeri Padang, 2023)
This research is made in the design of a database system and online sales files for sales on a medium business scale, Era 5.0 Society many marketplaces make it easy for medium businesses to sell products, So business actors need to see the development of digital business and forecast their merchandise that is sold out online. As for the implementation of 1) database from RDBMS into MYSQL. The research uses an open source database, namely MYSQL, 2) The research method uses Microsoft Access program tools with the link to the Windows 10 operating system odbc in Extract Transform Load (ETL) which is carried out automatically with button 3 process Extract, Transform, Load from the download folder into the relational database management system (RDMS) in ms access and stored in the MySQL database. 3) This research forms raw data facts from several marketplaces and is processed into normalized table dimensions in the data warehouse. This research aims to design a combination of open-source systems and Microsoft access licenses, for business actors who need sales analysis that is sold multichannel (online or offline), to optimize stock and provide products consistently in each sales channel.